Analysis of Power-to-Heat Units Penetration Effect on Dynamic Behavior of Power Distribution Grids - Oskouei, Morteza Zare; Erdinc, Fatma Gulsen; Erdinc, Ozan (IEEE, 2024)
The integration of power distribution grids with district heating networks, in conjunction with the deployment of power-to-heat (PtH) units, presents both significant challenges and opportunities for the dynamic behavior of power grids. This paper investigates the dynamic effects of PtH units on power distribution grids using DIgSILENT PowerFactory. The study employs a multidimensional approach, combining economic optimization with dynamic simulations using quasi-dynamic simulation, contingency analysis, and RMS simulation tools. The paper presents several case studies on the IEEE 33-bus test system, which evaluates the impact of PtH units on grid stability, feeder loading margin, and contingency situations under various conditions. The study reveals insights into the dynamic behavior of integrated energy networks, emphasizing the necessity of considering both static and dynamic aspects of integrated energy systems for effective grid management.
Keywords: DIgSILENT PowerFactory; dynamic characteristics; integrated energy networks; power-to-heat (PtH) units; stability of power grids; Energy & Fuels; Engineering